Peranan Perubahan Budaya Berjilbab Dalam Implementasi Strategi Dan Efeknya Terhadap Kinerja Bisnis Pada Usaha Kecil Jilbab - Suaibatul Aslamiyah; Mintarti Rahayu; Achmad Helmy Djawahir (Jurnal Manajemen dan Kewirausahaan, 2018)
This study aims to describe and explain the meaning of change in hijab culture in society and how the role of these values change on the implementation of differentiation-focus strategy and its effect in improving business performance. This research is conducted  on small business hijab Faiz Collection in Manyar District Gresik. This research approach is a case study with qualitative descriptive research method. The findings of the study indicate that the meaning of change in hijab culture is related to values on the hijab. The first value is cultural value, formed by: 1) religious system, 2) social     organization     system,            and 3) knowledge system. The second value is hijab value, formed by: 1) religious system, 2) community norms, 3) requirements, and 4) benefits. The third value is business value, formed by: 1) consumption activities, 2) production activities and 3) distribution activities. The effect of changing needs on hijab (from hijab standard to the syar'i hijab) to business performance is the increasing sales doubled compared with the standard hijab sales.  https://doi.org/10.26905/jmdk.v6i1.2151